The effect of pH on the hydrolytic degradation of poly(ε-caprolactone)-block-poly(ethylene glycol) copolymers - Loh, Xian Jun (Journal of applied polymer science, 2013)
The in‐vitro hydrolytic behavior of diblock copolymer films consisting of poly(ε‐caprolactone) (PCL) and poly(ethylene glycol) (PEG) was studied at pH 7.4 and pH 9.5 at 37°C. The degradation of these films was characterized at various time intervals by mass loss measurements, GPC, 1H‐NMR, DSC, FTIR, XRD, and SEM. A faster rate of degradation took place at pH 9.5 than at pH 7.4. Analysis of the molecular weight profile during the course of degradation revealed that random chain scission of the ester bonds in PCL predominates at the initial induction phase of polymer degradation. There was also an insignificant mass loss of the films observed. Mass spectroscopy was used to determine the nature of the water soluble products of degradation. At pH 7.4, a variety of oligomers with different numbers of repeating units were present whereas the harsher degradation conditions at pH 9.5 resulted in the formation of dimers. From the results, it can be proposed that a more complete understanding of the degradation behavior of the PCL‐b‐PEG copolymer can be monitored using a combination of physiological and accelerated hydrolytic degradation conditions. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013